2013
DOI: 10.1097/iae.0b013e3182845c39
|View full text |Cite
|
Sign up to set email alerts
|

Plus Disease Diagnosis in Retinopathy of Prematurity

Abstract: Purpose To examine vascular tortuosity as a function of distance from the optic disc in infants with retinopathy of prematurity (ROP). Methods 34 wide-angle retinal images from infants with ROP were reviewed by 22 experts. A reference standard for each image was defined as the diagnosis (plus vs. not plus) given by the majority of experts. Tortuosity, defined as vessel length divided by straight-line distance between vessel endpoints, was calculated as a function of distance from the disc margin for arteries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…1 That said, numerous studies have shown that a variety of features beyond this standard definition may be considered by physicians while diagnosing plus disease. 12,33,38,43 To address this potential confounder for 12 of the 34 images, 3 experts were asked to re-classify all 34 of the original 2007 cropped images. The average score was not significantly different from their original 2016 gradings (2.60 vs. 2.67); however it was significantly more severe than the original 2007 scores (2.1).…”
Section: Discussionmentioning
confidence: 99%
“…1 That said, numerous studies have shown that a variety of features beyond this standard definition may be considered by physicians while diagnosing plus disease. 12,33,38,43 To address this potential confounder for 12 of the 34 images, 3 experts were asked to re-classify all 34 of the original 2007 cropped images. The average score was not significantly different from their original 2016 gradings (2.60 vs. 2.67); however it was significantly more severe than the original 2007 scores (2.1).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that inter-expert agreement in ROP classification is imperfect. However, most previous work has focused on plus disease 8,9,11,12,16 and zone classification. 7,19,20 In this study, the majority of discrepancies in stage classification were at the very mild ends of the disease spectrum (stage 0 vs. 1).…”
Section: Discussionmentioning
confidence: 99%
“…3 Also, the image possesses a narrow field of view (FOV), and does not reveal possible tortuous vessels in the periphery of the retina, which have recently been shown to be more correlated to the presence of plus disease. [10][11][12] The narrow FOV of the standard photograph is believed to represent the FOV of a funduscope when centered on the optic nerve head (ONH). However, to the best of the authors' knowledge, such a limit to the area of analysis has never been justified.…”
Section: Plus Diseasementioning
confidence: 99%
“…Furthermore, all mentioned studies limited the area of analysis to the posterior of the retina; however, peripheral-vessel tortuosity has been shown to be more correlated to the presence of plus disease as compared to posterior-vessel tortuosity. [10][11][12] The main focus of the present work is on the development of image processing methods for detection and quantitative analysis of abnormally tortuous vessels in retinal fundus images as well as an approach to use measures of tortuosity for diagnosis of plus disease. In addition to the results of quantification of tortuosity as a single diagnostic feature, the results of our previous related studies on the thickness 27 and the openness of the MTA 14 are used to perform feature selection and pattern classification.…”
Section: Plus Diseasementioning
confidence: 99%